INTERNAL AUDIT AS A MANAGEMENT AID TOOL IN SUPPORTING SERVICE IMPLEMENTATION AND HUMAN RESOURCES QUALITY - Chaerudin, Abdul Rauf; Zullaiqa, Nabila; Zakiyah, Nadhira (LPPM Universitas Bina Bangsa, 2023)
Given the limitations of a leader to control and supervise the activities of agencies led management must delegate some authority to his subordinates. Therefore the constraints that arise in the delivery of information on the activities delegated to subordinates. So it takes a part of the independent nature, referred to as internal audit agency. The problem that arises is whether the internal audit role in improving the implementation of quality of service and human resources. Starting from the above description, the authors are interested in discussing this issue with the initial conclusions as follows: